Comparative Outcome between Intracervical Catheterization and Vaginal Misoprostol in the Induction of Labour in Intrauterine Fetal Death - Hoque, Humaira; Walida, Salma Akhtar; Parvin, Salma; Sultana, Chowdhury Shamima; Wareshuzzaman, Md; Yasmeen, Mst Nilufar; Ara, Begum Hosne; Nahar, Shamsun (Ibrahim Cardiac Medical Journal, 2023)
Background & Objective: Induction of labour (ILO) is a standard obstetric approach to terminate the pregnancy. But it is always a challenge to many an obstetrician and is more so when the cervix is unfavourable. The intrauterine fetal death (IUFD) itself does not constitute an indication for cesarean section and surgery should be reserved for specific conditions, since it increases maternal morbidity without any fetal advantage. The present study was undertaken to make a comparative evaluation of the outcome of intracervical Foley’s catheter insertion and vaginal misoprostol in the induction of labour in pregnant women with IUFD. Methods: This study was a comparative cross-sectional study conducted in the Department of Obstetrics and Gynecology, Sir Salimullah Medical College & Mitford Hospital over a period of one year between January to December 2013. A total 68 single-tone pregnant women with gestational age > 24 weeks, intact membrane and IUFD confirmed by sonography were consecutively included in the study. However, cases with temperature > 38˚C, placenta previa, chorioamnionitis, vaginal bleeding were excluded from the study. The recruited patients were randomly assigned to intracervical catheterization (ICC) and vaginal misoprostol (VMP) groups. While the independent variable was induction of labour, the outcome variables were time to induction, interval from induction to full-dilatation and thinning of the cervix (effacement) and time needed from induction to delivery. Results: More than one-quarter (27.9%) of the patients were 20 or < 20 years. The patients were predominantly primipara (63.2%). Around two-thirds of the patients in either study groups received 10 – 20 units of oxytocin with no significant intergroup difference in terms of oxytocin needed (p = 0.793). The difference between the two groups in terms of pethidine needed to get rid of the labour pain was not statistically significant (p = 0.278). Time to induction in majority of the patients of both groups was 13 or < 13 hours and there was no significant difference between the groups in terms of time to induction (p = 0.380). About one-third (32.4%) of VMP group required < 15 hours from induction to full-dilatation (effacement) of cervix as opposed to only 11.8% of the ICC group (p = 0.014). Over half (52.9%) of the VMP group delivered their dead fetus in < 18 hours as compared to 41.2% of the ICC group (p = 0.331). Conclusion: The study concluded that vaginal misoprostol is more effective and safe for cervical ripening and labour induction than Foley’s catheter in pregnant women with IUFD. Type and amount of analgesia needed and oxytocin required between VMP and ICC groups do not differ significantly. Ibrahim Card Med J 2022; 12 (1): 25-29